Development of an Attachment Instrument for Boarding Students Based on the Phenomenon of Ghasab - Januarni Dwi Rachmayanti, Januarni Dwi Rachmayanti; Fatimah Az-Zahro, Fatimah Az-Zahro; Wulandari Ney, Wulandari Ney; Lisnawati Ruhaena, Lisnawati Ruhaena (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to develop a psychometric instrument, the Santri Friendship Attachment Scale (SFAS), to measure friendship attachment among boarding students (santri) in Indonesian pesantren, especially in the context of ghasab behavior, a normalized act of borrowing without permission. Employing a mixed-methods design, the research was conducted in five stages: qualitative interviews, expert validation using Aiken’s V, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and reliability testing. Initial qualitative data were gathered from santri and religious teachers to inform item development. Content validity was assessed by seven raters using Aiken’s V, resulting in 30 items exceeding the 0.70 threshold. EFA and CFA were conducted on data from 182 students across three pesantren using SPSS v23, revealing a final structure of 11 items across four factors: emotional support, brotherhood among friends, reciprocal relationships, and self-disclosure. The instrument demonstrated acceptable internal consistency (α = 0.728). The SFAS offers a valid and reliable tool to explore peer attachment and its influence on behavioral norms in communal educational settings.